Dengue rapid diagnostic tests: Health professionals' practices and challenges in Burkina Faso. (August 2018) - Zongo, Sylvie; Carabali, Mabel; Munoz, Marie; Ridde, Valéry
Objectives: Dengue fever remains unrecognized and under-reported in Africa due to several factors, including health professionals' lack of awareness, important prevalence of other febrile illnesses, most of which are treated presumptively as malaria, and the absence of surveillance systems. In Burkina Faso, health centers have no diagnostic tools to identify and manage dengue, which remains ignored, despite the evidence of seasonal outbreaks in recent years. A qualitative study was conducted to analyze the use of rapid diagnostic tests in six health and social promotion centers (i.e. health-care centers, from the French Centers de Santé et de Promotion Sociale ) of Ouagadougou (Burkina Faso) in an exploratory research context. Methods: Dengue rapid diagnostic tests were introduced into fever-related consultations from December 2013 to January 2014. In-depth individual interviews were conducted in May and June 2014 with 32 health professionals. Results: Prior to the introduction of the tests, dengue was not well known or diagnosed by health professionals during consultations. Most febrile cases were routinely presumed to be malaria and treated accordingly. With training and routine use of rapid diagnostic tests, health professionals became more knowledgeable about dengue, improving the diagnosis of non-malaria febrile cases and its management, and better prescription practices. Conclusions: In a context of dengue re-emergence and high prevalence of other febrile illnesses, having rapid diagnostic tools available, especially during epidemics reinforces health professionals' diagnostic and prescribing capacities, allowing an opportune and accurate case management and facilitates diseases surveillance.